Left atrial phasic function and heart rate variability in patients with systemic sclerosis: A new part of the old puzzle. Issue 10 (7th August 2017) - Tadic, Marijana; Zlatanovic, Maja; Cuspidi, Cesare; Stevanovic, Ana; Kocijancic, Vesna; Pavlovic, Sinisa U.; Damjanov, Nemanja; Celic, Vera
Abstract : Objective: We aimed to research left atrial (LA) phasic function and heart rate variability (HRV), as well as their relationship, in subjects with uncomplicated systemic sclerosis (SSc). Methods: The investigation involved 44 SSc patients and 33 age‐matched healthy controls. All participants underwent clinical examination, serological tests, 24‐hours Holter monitoring, and echocardiographic examination including strain analysis. Results: Maximum, minimum, and pre‐A LA volumes and volume indices were higher in the SSc patients than in the controls. The total emptying fraction, the parameter of the LA reservoir function, as well as passive LA emptying fraction, which represents the LA conduit function, were significantly lower in the SSc patients compared to the controls. Active LA emptying fraction, the parameter of the LA booster pump function, was significantly higher in the SSc participants. There was no difference in LA reservoir function between the diffuse and the limited SSc form. LA conduit function was significantly decreased, whereas LA booster pump function was compensatory increased in the diffuse SSc form compared to the limited SSc form. Similar results were obtained by LA strain analysis. HRV indices were significantly decreased in the SSc patients. Modified Rodnan skin score, the parameter of skin involvement in SSc, and HRV indices correlated well with LA phasic function in SSc. Conclusion: Left atrial (LA) phasic function, assessed by both volumetric and strain method, as well as cardiac autonomic nervous function is significantly deteriorated in SSc patients. Skin score and HRV indices correlate with LA phasic function parameters.